2018
DOI: 10.1186/s12959-018-0172-6
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human soluble thrombomodulin improves mortality in patients with sepsis especially for severe coagulopathy: a retrospective study

Abstract: BackgroundDisseminated intravascular coagulation (DIC) is associated with high mortality in patients with sepsis. Several studies reporting that recombinant human soluble thrombomodulin (rhTM) reduced mortality in sepsis patients. This retrospective cohort study aimed to evaluate the efficacy of rhTM for patients with mild coagulopathy compared with those with severe coagulopathy.MethodsWe evaluated about 90-day mortality and SOFA score. SOFA score was also evaluated for the following components: respiratory, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Hayakawa et al demonstrated that AT treatment in sepsis-induced DIC may be associated with a reduced in-hospital all-cause mortality [140]. Similarly a study be Kato et al suggested possible mortality benefit in septic patients with coagulopathy treated with recombinant thrombomodulin [141]. Although none of the studies with anticoagulants provide data as robust as the PROWESS trial studying activated protein C (APC), the benefit of using APC is offset with the increased risk for bleeding [142].…”
Section: Natural Anticoagulant Pathwaysmentioning
confidence: 99%
“…Hayakawa et al demonstrated that AT treatment in sepsis-induced DIC may be associated with a reduced in-hospital all-cause mortality [140]. Similarly a study be Kato et al suggested possible mortality benefit in septic patients with coagulopathy treated with recombinant thrombomodulin [141]. Although none of the studies with anticoagulants provide data as robust as the PROWESS trial studying activated protein C (APC), the benefit of using APC is offset with the increased risk for bleeding [142].…”
Section: Natural Anticoagulant Pathwaysmentioning
confidence: 99%
“…The study showed that the seven-day DIC score was improved in the treatment group, but the 28-day mortality was not significantly different. In this study, a sample size of 114 patients was supposed to provide 90% power at a 5% two-sided α level for the mortality, and 105 patients for the seven-day DIC resolution [13]. In our study, according to Cohen [35], a sample size of 79 patients or 84 patients provided 80% power at a 5% two-sided α level for the mortality or the DIC resolution.…”
Section: Discussionmentioning
confidence: 99%
“…The Sepsis Coagulopathy Asahi Recombinant LE Thrombomodulin (SCARLET) randomized clinical trial, an expanded phase III clinical trial of the phase IIb study, also failed to show the improvement of thrombomodulin in the 28-day all-cause mortality in the treatment of sepsis-associated DIC [12]. On the contrary, recent retrospective observational studies in Japan claimed that ART-123 might be beneficial to treat sepsis-induced DIC in patients with severe coagulopathy [13] or severe respiratory failure [14].…”
Section: Introductionmentioning
confidence: 99%
“…Yamakawa et al found that in a small group of patients with sepsis-induced DIC administration of rhTM resulted in significant improvement in organ dysfunction as marked by Sequential Organ Failure Assessment (SOFA) scores and a significant reduction in 28day mortality versus controls [37]. A subsequent study by Kato et al focused on septic patients with mild versus severe coagulopathy and, once again, found an improvement in SOFA scores, especially the respiratory component, and 90day mortality amongst those in the severe group [38]. However, the SCARLET trial, which was a randomized controlled trial involving over 800 patients with sepsis-associated coagulopathy, failed to show a benefit in terms of 28-day mortality (Table 1) [39].…”
Section: Article Highlightsmentioning
confidence: 99%